Identification and characterization of a brilliant yellow pigment produced by Bordetella pertussis. (11th October 2017) - Odanaka, Keita; Iwatsuki, Masato; Satho, Tomomitsu; Watanabe, Mineo
ABSTRACT: Culture supernatants of Bordetella pertussis are a brilliant yellow; however, the structure and biological role of the responsible pigment have not been investigated. In this study, a brilliant yellow‐colored fraction was extracted from culture supernatants of B. pertussis and analyzed by HPLC. UV–visible spectral analysis and mass spectrometry identified the brilliant yellow pigment as riboflavin. Riboflavin production was high in lag and early log phases and riboflavin was found to enhance growth of B. pertussis in low‐density cultures. Riboflavin production is not regulated by the BvgAS system. In addition, it was found that other Bordetella species, such as B. parapertussis, B. holmesii and B. bronchiseptica, also release riboflavin into their culture supernatants. This is the first report that B. pertussis secrets riboflavin to the extracellular space and that riboflavin may promote its growth. The mechanism may be associated with pathogenesis of B. pertussis .